Treatment of Functional Dyspepsia in Outpatients after COVID-19 Infection - M. S. Turchina; Yu. M. Morozov; T. I. Obolenskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to compare the efficacy of different therapeutic regimens for managing functional dyspepsia in outpatients after COVID-19 infection.Materials and methods. 42 post-COVID-19 outpatients (age: 26–47 years) diagnosed with functional dyspepsia (FD) according to the Rome IV Criteria were enrolled in two parallel groups. All patients were divided in 2 groups by randomization: Group 1 received omeprazole at a dose of 80 mg/day, Group 2 received a combination of omeprazole and Kolofort® (a combined action drug product containing technologically processed antibodies to S100, TNF-alpha, and histamine) at a dose of 80 mg/day. At baseline and after treatment, a 10-point VAS was used to measure symptoms and an SF-36 questionnaire to evaluate the quality of life.Results. By Day 28 of the treatment, the intensity of epigastric pain (VAS score) in the group receiving proton-pump inhibitor (PPI) + Kolofort® was significantly lower. In both groups, fully resolved dyspeptic syndrome was observed in up to 90 % of patients, without significant differences (p < 0.06). According to the SF-36 data, a combination treatment resulted in higher scores (pain and general health subscales) as compared to the PPI alone.Conclusion. Kolofort® relieves symptoms and improves the quality of life when added to the treatment regimen against functional dyspepsia in post-COVID-19 patients.